Is Chile a role model of export diversification policies? A reassessment; Es Chile un modelo en políticas de diversificación de exportaciones? Una reevaluación - Gonzales Salinas (Estudios de Economía, 2024)
Largely because of its vast copper reserves, Chile's exports are highly concentrated on this low complexity product and this is often cited as a major drawback of its economic policy framework. However, its exogenous copper abundance conceals the country's success in developing non-mineral and complex exports. This achievement is remarkable considering its remoteness from the large international economic centers, which limits its integration to global value chains. As suggested in this paper, this accomplishment reflects Chile's strength in policy areas that foster non-mineral exports (including complex exports), making the country a role model in export diversification policies among emerging market countries.
Keywords: F1; O1; O4; 330; International trade; economic growth; economic development; export diversification; export complexity